diff -r 2585e2a7a7ab -r 5c063eeda622 AFP-Submission/Regular_Set.thy --- a/AFP-Submission/Regular_Set.thy Tue Jun 14 12:37:46 2016 +0100 +++ /dev/null Thu Jan 01 00:00:00 1970 +0000 @@ -1,481 +0,0 @@ -(* Author: Tobias Nipkow, Alex Krauss, Christian Urban *) - -section "Regular sets" - -theory Regular_Set -imports Main -begin - -type_synonym 'a lang = "'a list set" - -definition conc :: "'a lang \ 'a lang \ 'a lang" (infixr "@@" 75) where -"A @@ B = {xs@ys | xs ys. xs:A & ys:B}" - -text {* checks the code preprocessor for set comprehensions *} -export_code conc checking SML - -overloading lang_pow == "compow :: nat \ 'a lang \ 'a lang" -begin - primrec lang_pow :: "nat \ 'a lang \ 'a lang" where - "lang_pow 0 A = {[]}" | - "lang_pow (Suc n) A = A @@ (lang_pow n A)" -end - -text {* for code generation *} - -definition lang_pow :: "nat \ 'a lang \ 'a lang" where - lang_pow_code_def [code_abbrev]: "lang_pow = compow" - -lemma [code]: - "lang_pow (Suc n) A = A @@ (lang_pow n A)" - "lang_pow 0 A = {[]}" - by (simp_all add: lang_pow_code_def) - -hide_const (open) lang_pow - -definition star :: "'a lang \ 'a lang" where -"star A = (\n. A ^^ n)" - - -subsection{* @{term "op @@"} *} - -lemma concI[simp,intro]: "u : A \ v : B \ u@v : A @@ B" -by (auto simp add: conc_def) - -lemma concE[elim]: -assumes "w \ A @@ B" -obtains u v where "u \ A" "v \ B" "w = u@v" -using assms by (auto simp: conc_def) - -lemma conc_mono: "A \ C \ B \ D \ A @@ B \ C @@ D" -by (auto simp: conc_def) - -lemma conc_empty[simp]: shows "{} @@ A = {}" and "A @@ {} = {}" -by auto - -lemma conc_epsilon[simp]: shows "{[]} @@ A = A" and "A @@ {[]} = A" -by (simp_all add:conc_def) - -lemma conc_assoc: "(A @@ B) @@ C = A @@ (B @@ C)" -by (auto elim!: concE) (simp only: append_assoc[symmetric] concI) - -lemma conc_Un_distrib: -shows "A @@ (B \ C) = A @@ B \ A @@ C" -and "(A \ B) @@ C = A @@ C \ B @@ C" -by auto - -lemma conc_UNION_distrib: -shows "A @@ UNION I M = UNION I (%i. A @@ M i)" -and "UNION I M @@ A = UNION I (%i. M i @@ A)" -by auto - -lemma conc_subset_lists: "A \ lists S \ B \ lists S \ A @@ B \ lists S" -by(fastforce simp: conc_def in_lists_conv_set) - -lemma Nil_in_conc[simp]: "[] \ A @@ B \ [] \ A \ [] \ B" -by (metis append_is_Nil_conv concE concI) - -lemma concI_if_Nil1: "[] \ A \ xs : B \ xs \ A @@ B" -by (metis append_Nil concI) - -lemma conc_Diff_if_Nil1: "[] \ A \ A @@ B = (A - {[]}) @@ B \ B" -by (fastforce elim: concI_if_Nil1) - -lemma concI_if_Nil2: "[] \ B \ xs : A \ xs \ A @@ B" -by (metis append_Nil2 concI) - -lemma conc_Diff_if_Nil2: "[] \ B \ A @@ B = A @@ (B - {[]}) \ A" -by (fastforce elim: concI_if_Nil2) - -lemma singleton_in_conc: - "[x] : A @@ B \ [x] : A \ [] : B \ [] : A \ [x] : B" -by (fastforce simp: Cons_eq_append_conv append_eq_Cons_conv - conc_Diff_if_Nil1 conc_Diff_if_Nil2) - - -subsection{* @{term "A ^^ n"} *} - -lemma lang_pow_add: "A ^^ (n + m) = A ^^ n @@ A ^^ m" -by (induct n) (auto simp: conc_assoc) - -lemma lang_pow_empty: "{} ^^ n = (if n = 0 then {[]} else {})" -by (induct n) auto - -lemma lang_pow_empty_Suc[simp]: "({}::'a lang) ^^ Suc n = {}" -by (simp add: lang_pow_empty) - -lemma conc_pow_comm: - shows "A @@ (A ^^ n) = (A ^^ n) @@ A" -by (induct n) (simp_all add: conc_assoc[symmetric]) - -lemma length_lang_pow_ub: - "ALL w : A. length w \ k \ w : A^^n \ length w \ k*n" -by(induct n arbitrary: w) (fastforce simp: conc_def)+ - -lemma length_lang_pow_lb: - "ALL w : A. length w \ k \ w : A^^n \ length w \ k*n" -by(induct n arbitrary: w) (fastforce simp: conc_def)+ - -lemma lang_pow_subset_lists: "A \ lists S \ A ^^ n \ lists S" -by(induction n)(auto simp: conc_subset_lists[OF assms]) - - -subsection{* @{const star} *} - -lemma star_subset_lists: "A \ lists S \ star A \ lists S" -unfolding star_def by(blast dest: lang_pow_subset_lists) - -lemma star_if_lang_pow[simp]: "w : A ^^ n \ w : star A" -by (auto simp: star_def) - -lemma Nil_in_star[iff]: "[] : star A" -proof (rule star_if_lang_pow) - show "[] : A ^^ 0" by simp -qed - -lemma star_if_lang[simp]: assumes "w : A" shows "w : star A" -proof (rule star_if_lang_pow) - show "w : A ^^ 1" using `w : A` by simp -qed - -lemma append_in_starI[simp]: -assumes "u : star A" and "v : star A" shows "u@v : star A" -proof - - from `u : star A` obtain m where "u : A ^^ m" by (auto simp: star_def) - moreover - from `v : star A` obtain n where "v : A ^^ n" by (auto simp: star_def) - ultimately have "u@v : A ^^ (m+n)" by (simp add: lang_pow_add) - thus ?thesis by simp -qed - -lemma conc_star_star: "star A @@ star A = star A" -by (auto simp: conc_def) - -lemma conc_star_comm: - shows "A @@ star A = star A @@ A" -unfolding star_def conc_pow_comm conc_UNION_distrib -by simp - -lemma star_induct[consumes 1, case_names Nil append, induct set: star]: -assumes "w : star A" - and "P []" - and step: "!!u v. u : A \ v : star A \ P v \ P (u@v)" -shows "P w" -proof - - { fix n have "w : A ^^ n \ P w" - by (induct n arbitrary: w) (auto intro: `P []` step star_if_lang_pow) } - with `w : star A` show "P w" by (auto simp: star_def) -qed - -lemma star_empty[simp]: "star {} = {[]}" -by (auto elim: star_induct) - -lemma star_epsilon[simp]: "star {[]} = {[]}" -by (auto elim: star_induct) - -lemma star_idemp[simp]: "star (star A) = star A" -by (auto elim: star_induct) - -lemma star_unfold_left: "star A = A @@ star A \ {[]}" (is "?L = ?R") -proof - show "?L \ ?R" by (rule, erule star_induct) auto -qed auto - -lemma concat_in_star: "set ws \ A \ concat ws : star A" -by (induct ws) simp_all - -lemma in_star_iff_concat: - "w : star A = (EX ws. set ws \ A & w = concat ws)" - (is "_ = (EX ws. ?R w ws)") -proof - assume "w : star A" thus "EX ws. ?R w ws" - proof induct - case Nil have "?R [] []" by simp - thus ?case .. - next - case (append u v) - moreover - then obtain ws where "set ws \ A \ v = concat ws" by blast - ultimately have "?R (u@v) (u#ws)" by auto - thus ?case .. - qed -next - assume "EX us. ?R w us" thus "w : star A" - by (auto simp: concat_in_star) -qed - -lemma star_conv_concat: "star A = {concat ws|ws. set ws \ A}" -by (fastforce simp: in_star_iff_concat) - -lemma star_insert_eps[simp]: "star (insert [] A) = star(A)" -proof- - { fix us - have "set us \ insert [] A \ EX vs. concat us = concat vs \ set vs \ A" - (is "?P \ EX vs. ?Q vs") - proof - let ?vs = "filter (%u. u \ []) us" - show "?P \ ?Q ?vs" by (induct us) auto - qed - } thus ?thesis by (auto simp: star_conv_concat) -qed - -lemma star_unfold_left_Nil: "star A = (A - {[]}) @@ (star A) \ {[]}" -by (metis insert_Diff_single star_insert_eps star_unfold_left) - -lemma star_Diff_Nil_fold: "(A - {[]}) @@ star A = star A - {[]}" -proof - - have "[] \ (A - {[]}) @@ star A" by simp - thus ?thesis using star_unfold_left_Nil by blast -qed - -lemma star_decom: - assumes a: "x \ star A" "x \ []" - shows "\a b. x = a @ b \ a \ [] \ a \ A \ b \ star A" -using a by (induct rule: star_induct) (blast)+ - - -subsection {* Left-Quotients of languages *} - -definition Deriv :: "'a \ 'a lang \ 'a lang" -where "Deriv x A = { xs. x#xs \ A }" - -definition Derivs :: "'a list \ 'a lang \ 'a lang" -where "Derivs xs A = { ys. xs @ ys \ A }" - -abbreviation - Derivss :: "'a list \ 'a lang set \ 'a lang" -where - "Derivss s As \ \ (Derivs s ` As)" - - -lemma Deriv_empty[simp]: "Deriv a {} = {}" - and Deriv_epsilon[simp]: "Deriv a {[]} = {}" - and Deriv_char[simp]: "Deriv a {[b]} = (if a = b then {[]} else {})" - and Deriv_union[simp]: "Deriv a (A \ B) = Deriv a A \ Deriv a B" - and Deriv_inter[simp]: "Deriv a (A \ B) = Deriv a A \ Deriv a B" - and Deriv_compl[simp]: "Deriv a (-A) = - Deriv a A" - and Deriv_Union[simp]: "Deriv a (Union M) = Union(Deriv a ` M)" - and Deriv_UN[simp]: "Deriv a (UN x:I. S x) = (UN x:I. Deriv a (S x))" -by (auto simp: Deriv_def) - -lemma Der_conc [simp]: - shows "Deriv c (A @@ B) = (Deriv c A) @@ B \ (if [] \ A then Deriv c B else {})" -unfolding Deriv_def conc_def -by (auto simp add: Cons_eq_append_conv) - -lemma Deriv_star [simp]: - shows "Deriv c (star A) = (Deriv c A) @@ star A" -proof - - have "Deriv c (star A) = Deriv c ({[]} \ A @@ star A)" - by (metis star_unfold_left sup.commute) - also have "... = Deriv c (A @@ star A)" - unfolding Deriv_union by (simp) - also have "... = (Deriv c A) @@ (star A) \ (if [] \ A then Deriv c (star A) else {})" - by simp - also have "... = (Deriv c A) @@ star A" - unfolding conc_def Deriv_def - using star_decom by (force simp add: Cons_eq_append_conv) - finally show "Deriv c (star A) = (Deriv c A) @@ star A" . -qed - -lemma Deriv_diff[simp]: - shows "Deriv c (A - B) = Deriv c A - Deriv c B" -by(auto simp add: Deriv_def) - -lemma Deriv_lists[simp]: "c : S \ Deriv c (lists S) = lists S" -by(auto simp add: Deriv_def) - -lemma Derivs_simps [simp]: - shows "Derivs [] A = A" - and "Derivs (c # s) A = Derivs s (Deriv c A)" - and "Derivs (s1 @ s2) A = Derivs s2 (Derivs s1 A)" -unfolding Derivs_def Deriv_def by auto - -lemma in_fold_Deriv: "v \ fold Deriv w L \ w @ v \ L" - by (induct w arbitrary: L) (simp_all add: Deriv_def) - -lemma Derivs_alt_def: "Derivs w L = fold Deriv w L" - by (induct w arbitrary: L) simp_all - - -subsection {* Shuffle product *} - -fun shuffle where - "shuffle [] ys = {ys}" -| "shuffle xs [] = {xs}" -| "shuffle (x # xs) (y # ys) = - {x # w | w . w \ shuffle xs (y # ys)} \ - {y # w | w . w \ shuffle (x # xs) ys}" - -lemma shuffle_empty2[simp]: "shuffle xs [] = {xs}" - by (cases xs) auto - -lemma Nil_in_shuffle[simp]: "[] \ shuffle xs ys \ xs = [] \ ys = []" - by (induct xs ys rule: shuffle.induct) auto - -definition Shuffle (infixr "\" 80) where - "Shuffle A B = \{shuffle xs ys | xs ys. xs \ A \ ys \ B}" - -lemma shuffleE: - "zs \ shuffle xs ys \ - (zs = xs \ ys = [] \ P) \ - (zs = ys \ xs = [] \ P) \ - (\x xs' z zs'. xs = x # xs' \ zs = z # zs' \ x = z \ zs' \ shuffle xs' ys \ P) \ - (\y ys' z zs'. ys = y # ys' \ zs = z # zs' \ y = z \ zs' \ shuffle xs ys' \ P) \ P" - by (induct xs ys rule: shuffle.induct) auto - -lemma Cons_in_shuffle_iff: - "z # zs \ shuffle xs ys \ - (xs \ [] \ hd xs = z \ zs \ shuffle (tl xs) ys \ - ys \ [] \ hd ys = z \ zs \ shuffle xs (tl ys))" - by (induct xs ys rule: shuffle.induct) auto - -lemma Deriv_Shuffle[simp]: - "Deriv a (A \ B) = Deriv a A \ B \ A \ Deriv a B" - unfolding Shuffle_def Deriv_def by (fastforce simp: Cons_in_shuffle_iff neq_Nil_conv) - -lemma shuffle_subset_lists: - assumes "A \ lists S" "B \ lists S" - shows "A \ B \ lists S" -unfolding Shuffle_def proof safe - fix x and zs xs ys :: "'a list" - assume zs: "zs \ shuffle xs ys" "x \ set zs" and "xs \ A" "ys \ B" - with assms have "xs \ lists S" "ys \ lists S" by auto - with zs show "x \ S" by (induct xs ys arbitrary: zs rule: shuffle.induct) auto -qed - -lemma Nil_in_Shuffle[simp]: "[] \ A \ B \ [] \ A \ [] \ B" - unfolding Shuffle_def by force - -lemma shuffle_Un_distrib: -shows "A \ (B \ C) = A \ B \ A \ C" -and "A \ (B \ C) = A \ B \ A \ C" -unfolding Shuffle_def by fast+ - -lemma shuffle_UNION_distrib: -shows "A \ UNION I M = UNION I (%i. A \ M i)" -and "UNION I M \ A = UNION I (%i. M i \ A)" -unfolding Shuffle_def by fast+ - -lemma Shuffle_empty[simp]: - "A \ {} = {}" - "{} \ B = {}" - unfolding Shuffle_def by auto - -lemma Shuffle_eps[simp]: - "A \ {[]} = A" - "{[]} \ B = B" - unfolding Shuffle_def by auto - - -subsection {* Arden's Lemma *} - -lemma arden_helper: - assumes eq: "X = A @@ X \ B" - shows "X = (A ^^ Suc n) @@ X \ (\m\n. (A ^^ m) @@ B)" -proof (induct n) - case 0 - show "X = (A ^^ Suc 0) @@ X \ (\m\0. (A ^^ m) @@ B)" - using eq by simp -next - case (Suc n) - have ih: "X = (A ^^ Suc n) @@ X \ (\m\n. (A ^^ m) @@ B)" by fact - also have "\ = (A ^^ Suc n) @@ (A @@ X \ B) \ (\m\n. (A ^^ m) @@ B)" using eq by simp - also have "\ = (A ^^ Suc (Suc n)) @@ X \ ((A ^^ Suc n) @@ B) \ (\m\n. (A ^^ m) @@ B)" - by (simp add: conc_Un_distrib conc_assoc[symmetric] conc_pow_comm) - also have "\ = (A ^^ Suc (Suc n)) @@ X \ (\m\Suc n. (A ^^ m) @@ B)" - by (auto simp add: le_Suc_eq) - finally show "X = (A ^^ Suc (Suc n)) @@ X \ (\m\Suc n. (A ^^ m) @@ B)" . -qed - -lemma Arden: - assumes "[] \ A" - shows "X = A @@ X \ B \ X = star A @@ B" -proof - assume eq: "X = A @@ X \ B" - { fix w assume "w : X" - let ?n = "size w" - from `[] \ A` have "ALL u : A. length u \ 1" - by (metis Suc_eq_plus1 add_leD2 le_0_eq length_0_conv not_less_eq_eq) - hence "ALL u : A^^(?n+1). length u \ ?n+1" - by (metis length_lang_pow_lb nat_mult_1) - hence "ALL u : A^^(?n+1)@@X. length u \ ?n+1" - by(auto simp only: conc_def length_append) - hence "w \ A^^(?n+1)@@X" by auto - hence "w : star A @@ B" using `w : X` using arden_helper[OF eq, where n="?n"] - by (auto simp add: star_def conc_UNION_distrib) - } moreover - { fix w assume "w : star A @@ B" - hence "EX n. w : A^^n @@ B" by(auto simp: conc_def star_def) - hence "w : X" using arden_helper[OF eq] by blast - } ultimately show "X = star A @@ B" by blast -next - assume eq: "X = star A @@ B" - have "star A = A @@ star A \ {[]}" - by (rule star_unfold_left) - then have "star A @@ B = (A @@ star A \ {[]}) @@ B" - by metis - also have "\ = (A @@ star A) @@ B \ B" - unfolding conc_Un_distrib by simp - also have "\ = A @@ (star A @@ B) \ B" - by (simp only: conc_assoc) - finally show "X = A @@ X \ B" - using eq by blast -qed - - -lemma reversed_arden_helper: - assumes eq: "X = X @@ A \ B" - shows "X = X @@ (A ^^ Suc n) \ (\m\n. B @@ (A ^^ m))" -proof (induct n) - case 0 - show "X = X @@ (A ^^ Suc 0) \ (\m\0. B @@ (A ^^ m))" - using eq by simp -next - case (Suc n) - have ih: "X = X @@ (A ^^ Suc n) \ (\m\n. B @@ (A ^^ m))" by fact - also have "\ = (X @@ A \ B) @@ (A ^^ Suc n) \ (\m\n. B @@ (A ^^ m))" using eq by simp - also have "\ = X @@ (A ^^ Suc (Suc n)) \ (B @@ (A ^^ Suc n)) \ (\m\n. B @@ (A ^^ m))" - by (simp add: conc_Un_distrib conc_assoc) - also have "\ = X @@ (A ^^ Suc (Suc n)) \ (\m\Suc n. B @@ (A ^^ m))" - by (auto simp add: le_Suc_eq) - finally show "X = X @@ (A ^^ Suc (Suc n)) \ (\m\Suc n. B @@ (A ^^ m))" . -qed - -theorem reversed_Arden: - assumes nemp: "[] \ A" - shows "X = X @@ A \ B \ X = B @@ star A" -proof - assume eq: "X = X @@ A \ B" - { fix w assume "w : X" - let ?n = "size w" - from `[] \ A` have "ALL u : A. length u \ 1" - by (metis Suc_eq_plus1 add_leD2 le_0_eq length_0_conv not_less_eq_eq) - hence "ALL u : A^^(?n+1). length u \ ?n+1" - by (metis length_lang_pow_lb nat_mult_1) - hence "ALL u : X @@ A^^(?n+1). length u \ ?n+1" - by(auto simp only: conc_def length_append) - hence "w \ X @@ A^^(?n+1)" by auto - hence "w : B @@ star A" using `w : X` using reversed_arden_helper[OF eq, where n="?n"] - by (auto simp add: star_def conc_UNION_distrib) - } moreover - { fix w assume "w : B @@ star A" - hence "EX n. w : B @@ A^^n" by (auto simp: conc_def star_def) - hence "w : X" using reversed_arden_helper[OF eq] by blast - } ultimately show "X = B @@ star A" by blast -next - assume eq: "X = B @@ star A" - have "star A = {[]} \ star A @@ A" - unfolding conc_star_comm[symmetric] - by(metis Un_commute star_unfold_left) - then have "B @@ star A = B @@ ({[]} \ star A @@ A)" - by metis - also have "\ = B \ B @@ (star A @@ A)" - unfolding conc_Un_distrib by simp - also have "\ = B \ (B @@ star A) @@ A" - by (simp only: conc_assoc) - finally show "X = X @@ A \ B" - using eq by blast -qed - -end